Hepatitis C virus treatment by direct-acting antivirals in successfully treated hepatocellular carcinoma and possible mutual impact. Issue 8 (August 2018) - Hassany, Mohamed; Elsharkawy, Aisha; Maged, Amr; Mehrez, Mai; Asem, Noha; Gomaa, Ahmed; Mostafa, Zeinab; Abbas, Bahaa; Soliman, Mohamad; Esmat, Gamal
Abstract : Background and aims: Treatment of hepatitis C virus (HCV) after successfully treated hepatocellular carcinoma (HCC) becomes possible with the introduction of direct-acting antivirals because of their favorable efficacy, safety, and short period of treatment. Few data are available on the results of treatment using different direct-acting antiviral regimens in successfully treated HCC and a lot of debate about its role in tumor recurrence. Methods: Sixty-two HCV-related HCC patients were enrolled in the study after successfully treated HCC; the studied population included either Child–Pugh 'A' or 'B7'. The patients were subcategorized to receive one of the following regimens: group 1: sofosbuvir (SOF)+ribavirin (RBV) for 24 weeks, group 2: SOF+simeprevir for 12 weeks, group 3: SOF+daclatasvir for 24 weeks, and group 4: SOF+daclatasvir+RBV for 12 weeks. The overall median follow-up period is 12 months after treatment initiation. Results: All treatment regimens were tolerable for all patients, with no reported major adverse events during treatment. The overall sustained virologic response rate was 64.5%, with the highest result in group 4 and the lowest result in group 1; 87.5 and 26.7%, respectively. HCC recurrence was observed in 42% of patients; 80.7% of these patients developed recurrence within 6 months of treatment initiation. Conclusion: Treatment of HCV in successfully treated HCC is feasible, with the best results achieved using multiple direct-acting antivirals and RBV; a high rate of HCC recurrence was observed, especially within the first 6 months of treatment initiation (ClinicalTrials.gov no: NCT02771405).